Past Times and Our Times: Reading Our Mutual Friend - David Paroissien (Cahiers Victoriens et Edouardiens)
Stories, Sissy Jupe knows, help people in trouble, witness her confession about reading to her father when he was ‘down.’ Stories ‘kept him, many times, from what did him real harm,’ she reveals to Louisa Gradgrind, defying the ruling ethic of Stone Lodge never to wonder. Consolation, amusement, entrance into the past, the present or the future, characters reading either history or fiction in Our Mutual Friend read for a variety of motives, generally with improving results. Reading flourishes variously and vigorously, a human activity that extends far beyond lines of type as rivers, corpses, fires, clothes, blackboards, wills, hand-delivered notes, ornaments and furnishings are all read. Yet to be cut off from the world of print, is to live only half a life, a truth the illiterate Noddy Boffin immediately acts to correct when he inherits a fortune. The rapacious and grasping ballad-seller he engages to read to him proves an uncertain authority on matters of historical interpretation and comically loose with Roman names and pronunciation. But Wegg’s dogged reading of The Decline and Fall of the Roman Empire opens a new world to Boffin. While Wegg might take Gibbon ‘easy,’ Boffin reflects, to an old bird like himself, he suddenly realizes that he had no idea until encountering history aurally that ‘there were half so many Scarers in print.’ Similarly to past and present readers of Our Mutual Friend stories work their magic, entertaining, disturbing, educating and prompting questions of abiding philosophical resonance.